2022
DOI: 10.1111/jfpe.14106
|View full text |Cite
|
Sign up to set email alerts
|

Effects of extrusion process parameters on cooking characteristics and physicochemical, textural, thermal, pasting, microstructure, and nutritional properties of millet‐based extruded products: A review

Abstract: In the current century, consumers are more concerned about the quality and safety of food. They are focusing more on high nutritional value, tasty, and visually appealing food items which are available at low cost. Food industries are making a consistent effort in developing such food products from nutrition‐rich ingredients such as millet using the new technology of food processing such as extrusion. Millet is rich sources of protein, fiber, antioxidants, polyphenols, and micronutrients which make it an excel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 94 publications
2
22
0
Order By: Relevance
“…In extrudates, the pasting temperature is lower than in crude, because the gelatinization and structural degradation of starch during the extrusion process generates a lower swelling capacity so that the starch granule gelatinizes earlier. Previous researchers [ 52 , 53 ] obtained a similar trend in millet-based extruded products.…”
Section: Discussionsupporting
confidence: 70%
“…In extrudates, the pasting temperature is lower than in crude, because the gelatinization and structural degradation of starch during the extrusion process generates a lower swelling capacity so that the starch granule gelatinizes earlier. Previous researchers [ 52 , 53 ] obtained a similar trend in millet-based extruded products.…”
Section: Discussionsupporting
confidence: 70%
“…The lower peak viscosity of LGR is associated with the pre-gelatinization and degradation of starch during extrusion. Yadav et al [36] have stated that gelatinization and structural degradation of starch during the extrusion process reduce the swelling capacity and thereby, result in lower viscosity. Similar results were reported by Dalbhagat & Mishra [25] for fortified rice kernels and Hagenimana et al [37] for extruded rice flour.…”
Section: Pasting Propertiesmentioning
confidence: 99%
“…Moisture flashing during extrusion could have caused these cracks and voids in the LGR. During extrusion, a sudden flash of moisture causes expansion in the hot viscoelastic melt at the die opening, where bubbles grow and eventually rupture, resulting in a large number of voids [35,36]. The significantly shorter cooking time of LGR also reflects the formation of cracks and voids during extrusion process.…”
Section: Microstructurementioning
confidence: 99%
“…Extruded foods have been a topic of discussion in the food industry for many years and continue to be a popular and convenient food choice for many consumers. Some concerns have been raised regarding the nutritional quality and safety of extruded foods [ 8 , 9 ]. Extruded foods are made by processing a mixture of ingredients, such as grains and legumes, under high pressure and temperature to create a dough-like material that is then pushed through a die to give it a specific shape.…”
Section: Introductionmentioning
confidence: 99%
“…Extruded foods are made by processing a mixture of ingredients, such as grains and legumes, under high pressure and temperature to create a dough-like material that is then pushed through a die to give it a specific shape. One concern with extruded foods is that the high heat and pressure used during processing can cause a loss of nutrients, especially vitamins and bioactive compounds [ 8 , 9 ]. Additionally, some studies have suggested that certain compounds formed during the extrusion process may have negative health effects.…”
Section: Introductionmentioning
confidence: 99%